ANALISIS FRAMING SEPUTAR INEWS SIANG RCTI SEGMEN “PILIHAN INDONESIA 2019” - Tubagus Muhammad Rayhan (Inter Script : Journal of Creative Communication, 2020)
AbstractThis research is motivated by the existence of a democratic party in 2019, during those times the Seputar iNews Afternoon program made a special segment of political-specific news related to presidential candidates, vice presidential candidates and other political figures who were also part of important figures from the party period democracy. This study aims to find out how the framing of news or framing conducted by the Seputar iNews Siang program in the "Indonesia 2019 Choices" segment is then linked to Robert N. Entman's framing analysis and how the program constructs it. Literature review in this study includes mass media, news, media ideology, reality construction by mass media, framing analysis. The method used in this research is descriptive analysis method. In the descriptive method, researchers will explore or photograph social situations that will be studied thoroughly, broadly and deeply. Based on this research, the "Indonesia Choices 2019" segment has two aspects, namely selection of issues and highlighting certain aspects of an issue. The selection of issues displayed by the "Indonesia 2019 Choices" segment in the Around the iNews Afternoon program according to the RCTI editorial team is based on activities related to the 2019 general election theme. a program that is a language that expresses ideas with sentences, narratives, headlines that clarify the emphasis. Then the framing of the editorial team on an event and broadcast to a wide audience and agenda setting that makes the direction where the news editor during the specified time.                                                                                                    Keywords: Mass Media, Reality Construction, Framing, Indonesia's Selected Segments 2019